2014
DOI: 10.1128/jvi.00285-14
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Host Diversity and Geographic Distribution of Hantaviruses in Sub-Saharan Africa

Abstract: The recent discovery of hantaviruses in shrews and bats in West Africa suggests that other genetically distinct hantaviruses exist in East Africa. Genetic and phylogenetic analyses of newfound hantaviruses, detected in archival tissues from the Geata mouse shrew (Myosorex geata) and Kilimanjaro mouse shrew (Myosorex zinki) captured in Tanzania, expands the host diversity and geographic distribution of hantaviruses and suggests that ancestral shrews and/or bats may have served as the original mammalian hosts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…Multiple alignment of amino acid sequences of all known hantaviruses show that both Asp residues in the nucleocapsid protein are highly conserved. Indeed, testing natively purified His-tagged N protein of Kilimanjaro virus, a newly discovered shrew-borne hantavirus from Africa (Kang et al, 2014) confirmed our observations made with SNV-N and demonstrated strong DNA-specific nucleolytic activity (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…Multiple alignment of amino acid sequences of all known hantaviruses show that both Asp residues in the nucleocapsid protein are highly conserved. Indeed, testing natively purified His-tagged N protein of Kilimanjaro virus, a newly discovered shrew-borne hantavirus from Africa (Kang et al, 2014) confirmed our observations made with SNV-N and demonstrated strong DNA-specific nucleolytic activity (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…Guo and colleagues [31] also recognized that shrews or moles could represent the ancestral host, although their data suggest bats with equal probability. Two independent methods support the basal position of TPMV and its sister taxa: Imjin virus (MJNV) in the Ussuri white-toothed shrew ( Crocidura lasiura ) [15], Uluguru virus (ULUV) in the Geata mouse shrew ( Myosorex geata ), and Kilimanjaro virus (KMJV) in the Kilimanjaro mouse shrew ( Myosorex zinki ) [54]. First, hantavirus sequences were aligned and rooted to another member of the family Bunyaviridae , Bunyamwera virus (type species of the Orthobunyavirus genus) for the glycoprotein- coding region, or M segment (the only segment reliably alignable with other genera in the family) [55], and maximum-likelihood phylogenetic estimation placed this shrew-borne lineage basal to the other hantaviruses relative to the Bunyamwera outgroup (Figure S1).…”
Section: New Hosts Discovered Redefining Hantavirus Evolutionary Tramentioning
confidence: 99%
“…In analyzing RNA, extracted from more than 1,500 tissues from nearly 50 shrew species collected throughout Europe, Asia, North America, and Africa, between 1980 and 2012, we have discovered multiple genetically distinct hantaviruses, including Seewis virus (SWSV) in the Eurasian common shrew [ 83 -86 ], Ash River virus (ARRV) in the masked shrew ( Sorex cinereus ) [ 87 ], Jemez Springs virus (JMSV) in the dusky shrew ( Sorex monticolus ) [ 87 ], Kenkeme virus (KKMV) in the fl at-skulled shrew ( Sorex roboratus ) [ 88 ], Amga virus (MGAV) in the Laxmann's shrew ( Sorex caecutiens ) [ 89 ], Sarufutsu virus (SRFV) in the long-clawed shrew ( Sorex unguiculatus ) [ 90 ], Cao Bang virus (CBNV) in the Chinese mole shrew ( Anourosorex squamipes ) [ 91 ], Xinyi virus (XYIV) in the Taiwanese mole shrew ( Anourosorex yamanashi ) [ 92 ], Camp Ripley virus (RPLV) in the northern shorttailed shrew ( Blarina brevicauda ) [ 93 ], Iamonia virus (AMNV) in the southern short-tailed shrew ( Blarina carolinensis ) (unpublished), Boginia virus (BOGV) in the Eurasian water shrew [ 94 ], Azagny virus (AZGV) in the West African pygmy shrew ( Crocidura obscurior ) [ 95 ], Jeju virus (JJUV) in the Asian lesser whitetoothed shrew ( Crocidura shantungensis ) [ 96 ], Bowé virus (BOWV) in the Doucet's musk shrew ( Crocidura douceti ) [ 97 ], Uluguru virus (ULUV) in the geata mouse shrew ( Myosorex geata ) [ 98 ], and Kilimanjaro virus (KMJV) in the Kilimanjaro mouse shrew ( Myosorex zinki ) [ 98 ] (Table 9.2 ).…”
Section: Hantaviruses In Shrewsmentioning
confidence: 99%